2021
DOI: 10.12681/mms.27809
|View full text |Cite
|
Sign up to set email alerts
|

Is the local extinction of Pinna nobilis facilitating Pinna rudis recruitment?

Abstract: Until the late 2010s the spiny fan-mussel Pinna rudis shared habitat in many Mediterranean sites with Mediterranean endemic Pinna nobilis, which dominated in abundance but that has gone locally extinct in most of its distribution area due to a recent widespread disease outbreak. In the Columbretes Islands Marine Reserve (NW Mediterranean) both species coexisted until 2017, when P. nobilis populations completely disappeared. In spring 2021 we revisited 7 permanent plots covering 1,485 m2 that had been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In the present scenario, it is interesting to observe that some ecological niches left vacant by P. nobilis following mass mortality are now being partially occupied by P. rudis . Kersting and Ballesteros [ 101 ] documented a behavioural shift in P. rudis populations in the Columbretes Islands Marine Reserve off the Iberian Mediterranean coast. Their study revealed a significant increase in the recruitment rates for P. rudis after the mass mortality event of P. nobilis in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In the present scenario, it is interesting to observe that some ecological niches left vacant by P. nobilis following mass mortality are now being partially occupied by P. rudis . Kersting and Ballesteros [ 101 ] documented a behavioural shift in P. rudis populations in the Columbretes Islands Marine Reserve off the Iberian Mediterranean coast. Their study revealed a significant increase in the recruitment rates for P. rudis after the mass mortality event of P. nobilis in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Kersting and Ballesteros 30 have suggested that other species, such as P. rudis, could benefit from the collapse of the P. nobilis population. During our surveys, only 5 specimens of P. rudis were found, located in 2 sites, but it must be considered that the survey was carried out only a short time after the MME of P. nobilis.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the Mediterranean, where P. nobilis does not occur, P. rudis can live indifferently on sandy, rocky and muddy substrata [8]. In the Mediterranean, the two species have different habitat preferences: P. nobilis inhabits sandy bottoms and seagrass meadows [9], P. rudis rocky bottoms [10], which may indicate the outcome of interspecific competition [11]. Occasionally, the two species have been seen to coexist, resulting in mixed populations normally dominated by P. nobilis [10].…”
mentioning
confidence: 99%
“…P. rudis has received less attention than its endemic sister species: the few studies available describe its Mediterranean populations as stable despite being characterised by low densities [10]. However, as its more iconic sister [12,13], P. rudis has been listed in Annex II of the Bern Convention as strictly protected species and in the Barcelona Convention as threatened or endangered marine species [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation